A configuration and contingency analysis of the development chain. (June 2017) - Primus, Dirk J.
Abstract: The area where product development (PD) and the supply chain (SC) intersect and interact to support new product introductions (NPI), the development chain (DC), is still under-researched territory. Based on a PD/SC interface with multiple sub-process connections, this study uses a configuration approach to classify project-level observations into DC groups with similar patterns of implementation. Further, the relationship between DC groups, contextual factors and NPI performance is investigated. In a sample of 124 NPI projects, four DC groups with distinct configurations are detected that interact with context in terms of industry clock-speed, annual firm revenue, product architecture complexity, agility of the product delivery strategy and newness. The results indicate that deliberate management of the PD/SC interface as a bundle of interrelated sub-process connections and careful alignment with the contextual terrain can benefit NPI performance. Overall, this article contributes to the body of knowledge concerned with NPI through vital insight into current practice at the interface of PD and SC. Further, it is envisaged that the detailed characterizations of the DC configurations and their interaction with context provided in this study serve to guide the purposeful management of the DC, as well as future research in this important area. Highlights: The article provides vital insight into practice at the interface of PD and the SC. It identifies four DC configurations that interact with context. Results indicate that deliberate management of the DC can benefit NPI performance.